2021
DOI: 10.1007/s11596-021-2325-2
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Microtubule Associated Serine/threonine Kinase Like Expression Inhibits Gastric Cancer Cell Growth and Induces Apoptosis by Activation of ERK1/2 and Inactivation of NF-κB Signaling

Abstract: SummaryMicrotubule-associated serine/threonine kinase (MASTL) functions to regulate chromosome condensation and mitotic progression. Therefore, aberrant MASTL expression is commonly implicated in various human cancers. This study analyzed MASTL expression in gastric cancer vs. adjacent normal tissue for elucidating the association with clinicopathological data from patients. This work was then extended to investigate the effects of MASTL knockdown on tumor cells in vitro. The level of MASTL expression in gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Studies investigated MASTL to be an important drug target for anticancer treatment due to its multifarious roles such as cellular transformation, metastasis, chromosomal instability, and the DNA damage response in various cancers [10,11,24]. MASTL is reported to be upregulated in several cancer cell lines including breast cancer cells [4,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigated MASTL to be an important drug target for anticancer treatment due to its multifarious roles such as cellular transformation, metastasis, chromosomal instability, and the DNA damage response in various cancers [10,11,24]. MASTL is reported to be upregulated in several cancer cell lines including breast cancer cells [4,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Another common immunosuppressive molecule, NF-κB, is widely found in tumour cells of the digestive system and participates in immune escape mainly by affecting the function of T cells. In a study on the effect of microtubule-associated serine/threonine kinase (MAST1) on gastric malignant tumours, it was found that tumour cells after MAST1 gene knockout exerted an antitumour effect by downregulating the expression of NF-κB p65, suggesting that NF-κB may be involved in the immune escape of tumour cells[ 79 , 80 ]. NF-κB1 p50 (hereinafter referred to as p50) realizes the immune escape of tumour cells by affecting the transcription of effector T cells at the cellular transcriptional level[ 81 , 82 ].…”
Section: Immunosuppressive Molecules Involved In Immune Escapementioning
confidence: 99%